FACTORS AFFECTING FINANCIAL DISTRESS IN FINANCIAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019-2023 - Bambang Arjuna Putra; Rico Nur Ilham; Ghazali Syamni; Zulfan (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to examine the effect of firm growth, operating cash flow, profitability, and firm size on financial distress in financial sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research employs a quantitative method with a sample of 93 companies selected through purposive sampling from a total population of 105 companies. Data were obtained from financial statements and analyzed using panel data regression with EViews 13. The findings reveal that firm growth and profitability have a significant negative effect on financial distress, while operating cash flow shows no significant effect. In contrast, firm size has a significant positive effect on financial distress. This study is expected to serve as a reference for management in financial sector companies to consider these indicators as benchmarks in assessing the potential risk of financial distress.